Saponins Effect on Human Insulin Amyloid Aggregation - Eleonora Mari; Silvia Vilasi; Paolo Moretti; Maria Rosalia Mangione; Giorgia Giorgini; Roberta Galeazzi; Maria Grazia Ortore (Biomolecules)
The misfolding and amyloid aggregation of proteins have been attracting scientific interest for a few decades, due to their link with several diseases, particularly neurodegenerative diseases. Proteins can assemble and result in insoluble aggregates that, together with intermediate oligomeric species, modify the extracellular environment. Many efforts have been and are devoted to the search for cosolvents and cosolutes able to interfere with amyloid aggregation. In this work, we intensively study the effect of saponins, bioactive compounds, on human insulin aggregation. To monitor the kinetic of amyloid aggregation following secondary structure changes, we perform fluorescence and UV-Visible absorption spectroscopies, using Thioflavin T and Congo Red as amyloid specific probes, and Circular Dichroism. To study the overall structural features and size of aggregates, we perform Synchrotron Small-Angle X-ray Scattering and Dynamic Light Scattering experiments. The morphology of the aggregates was assessed by Atomic Force Microscopy. To deepen the understanding of the saponins interaction with insulin, a Molecular Dynamics investigation is performed, too. The reported data demonstrate that saponins interfere with the amyloid aggregation by inducing a strong inhibition on the formation of insulin fibrils, likely through specific interactions with insulin monomers. A dose-dependent effect is evident, and amyloid inhibition is already clear when saponins are just 0.01% w/w in solution. We suggest that saponins, which are natural metabolites present in a wide range of foods ranging from grains, pulses, and green leaves to sea stars and cucumbers, can be promising metabolites to inhibit human insulin aggregation. This basic research work can pave the way to further investigations concerning insulin amyloidosis, suggesting the use of saponins as amyloid inhibitors and/or stabilizing agents in solution.